2013
DOI: 10.1007/s40257-013-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Diagnosis, and Therapeutic Management of Granuloma Annulare: An Update

Abstract: Granuloma annulare (GA) is a common cutaneous disorder classically presenting as annular groups of skin-colored to erythematous papules without epidermal change localized to the dorsal hands and/or feet. In addition to the localized form, there are variants including generalized (including generalized annular GA, disseminated papular GA, and atypical generalized GA), subcutaneous, and perforating GA, providing for a wide spectrum of clinical lesions. The etiology of GA remains unknown and several systemic asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
176
1
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(212 citation statements)
references
References 117 publications
3
176
1
17
Order By: Relevance
“…2 Historically, they have been considered to be closely associated with diabetes mellitus; more recently the strength of the association has been questioned. [3][4][5] …”
Section: Introductionmentioning
confidence: 99%
“…2 Historically, they have been considered to be closely associated with diabetes mellitus; more recently the strength of the association has been questioned. [3][4][5] …”
Section: Introductionmentioning
confidence: 99%
“…3,4 A variety of infectious agents have been implicated, including tuberculosis, Borrelia, varicella, EBV, hepatitis B and C and HIV. 4,5 Sun exposure and phototherapy with psoralen combined with ultraviolet A are also reported to precipitate GA. 4,6 Reported drug causes of GA included amlodipine, gold, allopurinol, diclofenac, quinidine, intra-nasal calcitonin and anti-tumour necrosis factor (TNF) agents. 6,7 In one study 15% of patients attributed onset of GA to psychological stress.…”
Section: Aetiologymentioning
confidence: 99%
“…4,5 Sun exposure and phototherapy with psoralen combined with ultraviolet A are also reported to precipitate GA. 4,6 Reported drug causes of GA included amlodipine, gold, allopurinol, diclofenac, quinidine, intra-nasal calcitonin and anti-tumour necrosis factor (TNF) agents. 6,7 In one study 15% of patients attributed onset of GA to psychological stress. 5 It has been suggested that GA is due to a delayed type hypersensitivity reaction, 5 but other theories have also been proposed.…”
Section: Aetiologymentioning
confidence: 99%
See 2 more Smart Citations